MILITARY SERVICE PRIDE: NATIONAL UNITY AND SECURITY - Shoimov Odil Kasimovich (American Journals Publishing, 2023)
This annotation summarizes the topic of the pride of the military service, its role in ensuring national solidarity and security. In the formation of a sense of national unity, military service plays an extremely important role in ensuring the security of the nation. This article explores how tolerance and self-sacrifice made by military personnel contribute to a cohesive society and highlights their role in protecting the people from external threats. He explores the sense of pride that comes from serving his country, which can shape a collective self and dedication to the welfare of the people. This article explores the role of the military in ensuring both national solidarity and security, clarifying the necessary contributions of service members in maintaining the welfare and stability of the nation.
Keywords: Pride, security, military service, identity, national idea.